Modern approaches to cervical cancer screening (a review) - M. I. Pavliuchenko; Yu. Ya. Krut; V. H. Siusiuka; O. V. Deinichenko (Zaporozhye State Medical University, 2023)
The aim - systematization of data from modern scientific sources and own knowledge and experience regarding the problems, advantages and prospects of the development of various methods of diagnosing pathological conditions of the cervix. The relevance of the problem of cervical cancer is beyond doubt, which is confirmed by the annual data of the official statistics and recommendations of WHO, European experts and relevant national recommendations. The analysis and generalization of information from the specialized literature regarding the assessment of problems and prospects for the development of leading methods of cervical screening in order to reduce the number of cervical cancer cases in the world is a priority task of the expert society. Currently, the most recommended approach to cervical screening is to combine HPV testing with cytology but separate testing for HPV is the most promising. Colposcopy remains the only confirmatory method of diagnosing cervical pathology, subject to mandatory cervical biopsy and histopathological examination of the biopsy. Standardization of classifications and terminology in the assessment of cytological, histopathological and colposcopic conclusions will allow to reach an understanding in the issues of optimal management tactics for patients with cervical pathology. Conclusions. Diagnosis of high-risk carcinogenic types of human papillomavirus is the most promising method of cervical screening in the near future. At the same time, at the moment, we consider it appropriate to use the cytology together with HPV testing, at least as a sorting method. Standardization of cytological/histopathological terminology should be done in accordance with the Bethesda 2014 system update.